An Integrated Collaborative Approach for Facilities Management- Sydney Opera House FM Exemplar - Morris, Jason; Ballesty, Stephen; Lan, Ding; Drogemuller, Robin; Mitchell, John; Schevers, Hans; Leifer, David; Schwede, Dirk; Wu, Jeremy; Henrikson, Janet; Akhurst, Paul; Spink, George (CRC for Construction Innovation, 2006)
This paper presents an integrated collaborative approach for facilities management (FM), which utilises the Sydney Opera House (SOH) as an exemplar case study. The approach deals with Benchmarking, Procurement and Digital Modelling as a whole and develops collaboration between them. It aims to achieve innovative FM strategies and models that will possibly have a direct benefit role for the Australian facilities management industry. The Benchmarking theme focuses on the asset maintenance of the performing art centre, iconic building and facilities with similar functionalities. Critical success factors in the functional areas of asset maintenance are identified against organisational objectives of the SOH and key performance indicators are developed. The Procurement theme focuses on the maintenance service procurement, especially for outsourcing. Procurement methods and a multi-criteria assessment approach for supporting decision making are discussed. Suggested collaboration between Benchmarking and Procurement includes sharing of the benchmarking data and utility of key performance indicators to support procurement strategies. The Digital Modelling theme develops building information modelling for facilities management and investigates the potential of state-of-the-art information systems to enable a future integrated platform to support facility management collaborative activities and processes. Keywords: facilities management, benchmarking, procurement, digital modelling